Study on the Spectrum-Effect Correlation of Anti-Inflammatory Active Extract of Sauropus spatulifolius Beille. (24th May 2022) - Qiu, Qin; Jiang, Lujuan; Huang, Chunying; Yu, Lifeng; Zhen, Dandan; Ye, Meifang; Liu, Yuanyuan; Shi, Junhao; Liu, Xiaofang; Gu, Baojun; Zhen, Hanshen
Abstract : Sauropus spatulifolius Beille ( S. spatulifolius ) is a commonly used medicine of the Bourau and Yao nationalities. However, the composition of S. spatulifolius is complex, and simple chemical fingerprints cannot accurately evaluate the relationship between its composition and efficacy. In this study, high-performance liquid chromatography (HPLC) method was used to establish the fingerprint of the ethyl acetate extract of S. spatulifolius . Based on the evaluation of the similarity of chromatographic fingerprints of traditional Chinese medicine, combined with cluster analysis and principal component analysis (PCA), the common peaks of fingerprints were evaluated. The anti-inflammatory effect data were extracted through the dimethylbenzene-induced ear-swelling model in mice. The gray relational analysis (GRA) combined with partial least squares regression (PLSR) was used to study the spectrum-effect correlation of S. spatulifolius . As a result, the HPLC fingerprint of the ethyl acetate extract of S. spatulifolius was established, and 18 common peaks were identified. Except for S6, the other similarities are all above 0.915. The reference substance control method was used to identify two absorption peaks, namely, protocatechuic acid and caffeic acid. The cluster analysis results showed that 10 samples from different origins were grouped into four categories, which was consistent with the PCA results. Ethyl acetate extract of 10 batches of S. spatulifolius could significantly inhibit the ear swelling of mice (P < 0.01 ). Through GRA, the order of the contribution of each chemical component to the anti-inflammatory efficacy was obtained. The results of PLSR showed that the VIP values of peaks 3, 4, and 12 were greater than 1 and were positively correlated with anti-inflammatory activity. In this study, the HPLC fingerprint of the ethyl acetate extract of S. spatulifolius was established. Through the study of the spectrum-effect correlation, the anti-inflammatory active substance of the ethyl acetate extract of S. spatulifolius was obtained. The anti-inflammatory effect of S. spatulifolius was the result of the joint action of multiple ingredients. This research helps to quickly and accurately discover the active ingredient groups of traditional Chinese medicine and provides new ideas and methods for studying the effective substances of traditional Chinese medicine.